Energy and momentum dependence of nuclear short-range correlations - Spectral function, exclusive scattering experiments and the contact formalism - Ronen Weiss; Igor Korover; Eli Piasetzky; Or Hen; Nir Barnea (Physics Letters B, 2019)
Results of electron-induced one- and two-nucleon hard knockout reactions, A(e,e′p) and A(e,e′pN), in kinematics sensitive to nuclear short-range correlations, are studied using the nuclear contact formalism. A relation between the spectral function and the nuclear contacts is derived and used to analyze the dependence of the data on the initial energy and momentum of the knocked-out proton. The ratio between the number of emitted proton-proton pairs and proton-neutron pairs is shown to depend predominantly on a single ratio of contacts. This ratio is expected to present deep minima in the initial energy and momentum plane, associated with the node in the proton-proton wave function.The formalism is applied to analyze data from recent 4He and 12C electron-scattering experiments performed at Jefferson laboratory. Different nucleon-nucleon potentials were used to assess the model-dependence of the results. For the ratio of proton-proton to proton-neutron pairs in 4He, a fair agreement with the experimental data is obtained using the two potentials, whereas for the ratio of proton-proton pairs to the total knocked-out protons in 12C, some of the features of the theory are not seen in the experimental data. Several possible explanations for this disagreement are discussed. It is also observed that the spectral function at specific domains of the momentum-energy plane is sensitive to the nucleon-nucleon interaction. Based on this sensitivity, it might be possible to constrain the short range part of the nuclear potential using such experimental data. Keywords: Short range correlations, Electron scattering, Spectral function, Contact formalism